T cell mediated immunity against influenza H5N1 nucleoprotein, matrix and hemagglutinin derived epitopes in H5N1 survivors and non-H5N1 subjects - Noisumdaeng, Pirom; Roytrakul, Thaneeya; Prasertsopon, Jarunee; Pooruk, Phisanu; Lerdsamran, Hatairat; Assanasen, Susan; Kitphati, Rungrueng; Auewarakul, Prasert; Puthavathana, Pilaipan (PeerJ (San Francisco, CA), 2021)
Protection against the influenza virus by a specific antibody is relatively strain specific; meanwhile broader immunity may be conferred by cell-mediated immune response to the conserved epitopes across influenza virus subtypes. A universal broad-spectrum influenza vaccine which confronts not only seasonal influenza virus, but also avian influenza H5N1 virus is promising. This study determined the specific and cross-reactive T cell responses against the highly pathogenic avian influenza A (H5N1) virus in four survivors and 33 non-H5N1 subjects including 10 H3N2 patients and 23 healthy individuals. Ex vivo IFN- ELISpot assay using overlapping peptides spanning the entire nucleoprotein (NP), matrix (M) and hemagglutinin (HA) derived from A/Thailand/1(KAN-1)/2004 (H5N1) virus was employed in adjunct with flow cytometry for determining T cell functions. Microneutralization (microNT) assay was performed to determine the status of previous H5N1 virus infection. IFN- ELISpot assay demonstrated that survivors nos. 1 and 2 had markedly higher T cell responses against H5N1 NP, M and HA epitopes than survivors nos. 3 and 4; and the magnitude of T cell responses against NP were higher than that of M and HA. Durability of the immunoreactivity persisted for as long as four years after disease onset. Upon stimulation by NP in IFN- ELISpot assay, 60% of H3N2 patients and 39% of healthy subjects exhibited a cross-reactive T cell response. The higher frequency and magnitude of responses in H3N2 patients may be due to blood collection at the convalescent phase of the patients. In H5N1 survivors, the effector peptide-specific T cells generated from bulk culture PBMCs by in vitro stimulation displayed a polyfunction by simultaneously producing IFN- and TNF- , together with upregulation of CD107a in recognition of the target cells pulsed with peptide or infected with rVac-NP virus as investigated by flow cytometry. This study provides an insight into the better understanding on the homosubtypic and heterosubtypic T cell-mediated immune responses in H5N1 survivors and non-H5N1 subjects. NP is an immunodominant target of cross-recognition owing to its high conservancy. Therefore, the development of vaccine targeting the conserved NP may be a novel strategy for influenza vaccine design.